Effect of an Educational Video Game for Diabetes Self-management on Adherence to a Self-care Regimen in Children with Type 1 Diabetes - Ebrahim Rafeezadeh; Nosrat Ghaemi; Hamid Heidarian Miri; Aramesh Rezaeian (Mashhad University of Medical Sciences, 2019)
Background: Type 1 diabetes is known as the most common endocrine disorder in children which requires strict adherence to self-care regimen. Accordingly, children's exposure to educational video games can be a strategy for promoting adherence to such regimens. Aim: The main purpose of this study was to investigate the effect of an educational video game for diabetes self-management on adherence to self-care regimens in children with type 1 diabetes. Method: This two-group randomized clinical trial was conducted on 68 children aged 8-12 years affected with type 1 diabetes and admitted to Akbar Children's Hospital in Mashhad, Iran, during 2018. A self-care package for children with type 1 diabetes was extracted using a review method. The intervention group played the designed interactive video game. Data were analyzed in SPSS software (version 16) through independent t-test and Mann Whitney U test. Results: Both study groups were homogeneous in terms of demographic characteristics. Based on the results of independent t-test, no significant difference was observed between the intervention (77.5±10.1) and control groups (78.7±7.4) regarding mean self-care scores before intervention (P=0.57). However, mean self-care score in the intervention group (82.9±7.8) was significantly higher than that in control group (77.3±7.7) after the intervention (P=0.57). Intra-group comparisons also confirmed the above-mentioned findings. Implications for Practice: The designed educational video game could significantly improve children's self-care scores. Given that Internet-based video games can be manipulated and quickly updated, it was suggested to compare online and offline video games in future studies.